The Impact Of Leadership To Serve And Organizational Commitments To Employee Performance With Behavior Organizational Citizenship as Mediation Variable - Eni Istikhomah Sholikhah; Septi Kurnia Prastiwi (Journal of Business and Management Review, 2020)
The aim of this study was to determine the influence of servant leadership and organizational commitment on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable (case study of the Center for Social Rehabilitation Prof. Dr. Soeharso Surakarta). The population in this study were employees of civil servants BBRSBD Prof. Dr. Soeharso Surakarta. With a sample used as many as 100 respondent. The technique of taking sample used is saturated sampling, where all populations are sampled entirely. Data collection techniques by distributing questionnaires. Data analysis techniques using Structural Equation Modeling (SEM) with the help of Partial Least Square (PLS) version 3.0. The results of the study show that 1) there is no significant influence of leadership variables that serve organizational citizenship behavior; 2) There is a significant influence of organizational commitment variables on organizational citizenship behavior; 3) There is influence of leadership variables that serve employee performance; 4) There is no influence on organizational commitment variables on employee performance; 5) There is an influence of organizational citizenship behavior variables on employee performance.